Method for relieving magnetic thermal degradation of magnetic core based on micro-nano flux bridge
By filling the magnetic powder core in the radio energy transmission technology to remove the air gap of the ferrite core, the magneto-thermal deterioration problem is solved, the magnetic leakage shielding ability and electromagnetic coupling of the magnetic core are improved, and the efficiency and safety of radio energy transmission are enhanced.
Patent Information
- Application Number
- CN202411806638.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
AI Technical Summary
In the existing radio energy transmission technology, the ferrite magnetic core deteriorates magnetothermal due to air gaps, which affects the safety and reliability of the system, and the existing mitigation methods have inconveniences and defects.
Through finite element multi-physical field magnetothermal simulation analysis, an array ferrite block magnetic core was made, and the magnetic permeable powder core was filled into the air gap. Finally, AB glue was injected into the magnetic permeable powder core to remove the air gap to form an air gapless magnetic core.
This method improves the magnetic leakage shielding ability of the magnetic core in the radio energy transmission magnetic coupling mechanism, weakens the boundary loss at the junction between ferrite magnetic blocks, alleviates the heating problem at the junction of magnetic blocks, and enhances electromagnetic coupling, improving radio energy transmission efficiency and output power.
Smart Images

Figure CN119694766A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wireless power transmission, and in particular to a method for alleviating magnetic thermal degradation of a magnetic core based on a micro-nano flux bridge. Background Art
[0002] Wireless power transfer (WPT) technology refers to a technology that uses the distribution or propagation characteristics of electromagnetic fields and electromagnetic waves in physical space to transfer electric energy from the power supply side to the load side without direct contact of wires. This technology is an important way to achieve flexible transmission and conversion of electric energy in various power usage scenarios where wired energy transmission is "not possible, not suitable, and not allowed."
[0003] Among them, ferrite material, as a core material widely used in WPT, is often assembled on the back of the coil to enhance the electromagnetic coupling of the system and reduce the leakage magnetic field. However, due to the processing technology and the brittle mechanical properties of ferrite itself, the size of the actual ferrite block is limited. Therefore, the ferrite blocks are usually arranged in an array to meet the size requirements of the WPT system core. However, in the splicing process of ferrite blocks, air gaps between ferrite blocks are inevitable. These air gaps significantly change the distribution of magnetic flux, causing a large amount of magnetic flux to gather at the air gap. The large amount of magnetic flux at the air gap not only increases the leakage flux at the air gap, but also causes overheating at the boundary of the ferrite air gap, resulting in hot spots. With the increase of wireless charging power level, the electromagnetic leakage and heat storage self-ignition problems at the ferrite air gap will become more and more prominent. This will affect the safety and reliability of long-term operation of high-power wireless power transmission systems.
[0004] The manganese-zinc ferrite materials currently used in the field of wireless charging are limited by the material properties and processing and manufacturing processes. The size of the sintered ferrite blocks is in the range of 2mm-150mm, mostly square blocks with a side length of 50mm and 100mm and a thickness of 2-5mm, or long strips with a length of 40mm, a width of 10mm and a thickness of 2-5mm. For wireless charging equipment with high requirements on size and shape, such as electric vehicles and underwater autonomous vehicles, it is still necessary to splice small-sized ferrite blocks in an array into a whole magnetic core for use. However, due to the limitations of processing steps such as annealing of ferrite materials, it cannot be guaranteed that each ferrite block is completely flat, and air gaps will inevitably exist during the splicing process of ferrite blocks.
[0005] In order to alleviate the magnetothermal problem on the array ferrite core, the existing technology starts from the core shape, ferrite block placement strategy and external heat dissipation measures. In order to reduce the internal magnetic flux of the ferrite core and reduce the core loss inside the ferrite, the researchers designed it into a stepped, E-shaped or U-shaped shape to balance the magnetic field to achieve the purpose of reducing losses. However, this increases the volume and weight of the original ferrite core, which is not conducive to the future development concept of lightweight integration of wireless charging equipment, and secondly, it does not solve the air gap problem. Although the I-type core is lightweight, its leakage magnetic suppression ability is limited due to too many air gaps. And by adjusting the air gap of the ferrite block and optimizing the size and placement of a single ferrite block to improve the magnetothermal characteristics on the ferrite core, it is also at the expense of a certain shielding effect of the core. In addition, by adding materials with high thermal conductivity such as epoxy resin to the WPT magnetic coupling mechanism or adding forced water cooling, air cooling and other heat dissipation measures, it can only alleviate the heating problem on the ferrite core, but cannot alleviate the leakage problem. There is also a technical solution of using nanocrystalline materials instead of ferrite materials, but the conductivity of nanocrystalline materials is much greater than that of ferrite materials, and the heating problem of nanocrystalline materials is more serious under the same power.
[0006] It can be seen that the above existing magnetic heat mitigation methods still have inconveniences and defects in use, and are in urgent need of further improvement. How to create a new magnetic core magnetic heat mitigation method has become a goal that the industry urgently needs to improve. Summary of the invention
[0007] In view of this, an embodiment of the present disclosure provides a method for alleviating magnetic thermal degradation of a magnetic core based on a micro-nano flux bridge, which at least partially solves the problems existing in the prior art.
[0008] In a first aspect, an embodiment of the present disclosure provides a method for alleviating magnetic thermal degradation of a magnetic core based on a micro-nano flux bridge, the method comprising the following steps:
[0009] Conduct finite element multi-physics field magnetic and thermal simulation analysis;
[0010] An array type ferrite magnetic block core is manufactured based on the simulation results;
[0011] Filling the air gap of the array-type ferrite magnetic block core with a magnetic powder core;
[0012] Injecting AB glue into the magnetic powder core to form a gapless magnetic core.
[0013] According to a specific implementation of the embodiment of the present disclosure, the method further includes:
[0014] Assemble the energy transmission coil;
[0015] Encapsulate the core and coil.
[0016] According to a specific implementation of the embodiment of the present disclosure, the finite element multi-physics field magnetothermal simulation analysis includes:
[0017] Calculate the relationship between the air gap width filled with magnetic powder, the relative magnetic permeability of the magnetic powder and the magnetocaloric properties of the ferrite core.
[0018] According to a specific implementation of the embodiment of the present disclosure, the relationship between the width of the air gap filled with magnetic conductive powder, the relative magnetic permeability of the magnetic conductive powder and the magnetocaloric properties on the ferrite core is calculated based on the following formula:
[0019]
[0020] Among them, T gm (l g ,μ gap ) is the edge temperature rise of the ferrite; p is the order of the air gap width; q is the order of the relative magnetic permeability of the powder core; k pq is the coefficient of the fitted polynomial function; l g is the air gap width; μ gap is the relative magnetic permeability of the medium in the air gap.
[0021] According to a specific implementation of the embodiment of the present disclosure, the method further includes:
[0022] The gap width of the ferrite block before filling and the magnetic powder core used to remove the air gap are selected based on the threshold of the ferrite edge temperature rise.
[0023] According to a specific implementation of the embodiment of the present disclosure, the gap width between the ferrite blocks is less than 0.4 mm.
[0024] According to a specific implementation of the embodiment of the present disclosure, the magnetic powder core is a FeSi6.5 nanocrystalline powder core.
[0025] The method for alleviating magnetic core magnetothermal degradation based on micro-nano flux bridge in the disclosed embodiment can improve the magnetic leakage shielding capability of the magnetic core in the wireless power transmission magnetic coupling mechanism, reduce the boundary (air gap) loss at the junction between the manganese-zinc ferrite magnetic blocks to alleviate the heating problem at the junction of the magnetic blocks, and at the same time enhance the electromagnetic coupling between the wireless power transmission transceiver coils, further improving the wireless power transmission efficiency and output power. It can effectively alleviate the magnetothermal degradation problem of the array ferrite core in the wireless power transmission magnetic coupling mechanism, and is particularly suitable for wireless charging equipment with high power level and high power density such as wireless charging of electric vehicles, and alleviates the severe thermal management problem caused by the high power level of the system. It has broad market prospects, strong adaptability, and wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0027] Figure 1 A schematic flow chart of a method for alleviating magnetic-thermal degradation of a magnetic core based on a micro-nano flux bridge provided in an embodiment of the present disclosure;
[0028] Figure 2 A schematic diagram of magnetic field propagation between ferrite blocks provided in an embodiment of the present disclosure;
[0029] Figure 3 is a schematic diagram of a cross-sectional model of an array-type ferrite magnetic block provided in an embodiment of the present disclosure;
[0030] Figure 4 is a schematic diagram of a powder core filling model provided by an embodiment of the present disclosure;
[0031] Figure 5 is a design and application flow chart of a magnetic coupling mechanism provided by an embodiment of the present disclosure;
[0032] Figure 6 The present invention provides a distribution diagram of the surface magnetic flux density and local temperature rise of a ferrite after using the present invention at a 0.3 mm air gap width.
[0033] Figure 7 This is a temperature rise distribution diagram of ferrite under a 0.1 mm air gap width when the present invention is not adopted, provided in an embodiment of the present disclosure;
[0034] Figure 8 This is a temperature rise distribution diagram of ferrite with a 0.1 mm air gap width when the present invention is used, provided by an embodiment of the present disclosure;
[0035] Fig. 9 It is a schematic diagram of leakage magnetic flux density using a reference line along the trailing edge of the present invention provided by an embodiment of the present disclosure;
[0036] Fig.10 It is an equivalent circuit diagram of a rear array ferrite magnetic coupling mechanism using the present invention provided by an embodiment of the present disclosure;
[0037] Fig.11 This is a schematic diagram of the variation of the mutual inductance of a post-harvesting system according to an embodiment of the present disclosure with the width of an air gap;
[0038] Fig.12 It is a schematic diagram of an array-type ferrite core with air gaps provided in an embodiment of the present disclosure;
[0039] Fig.13 is a schematic diagram of a high magnetic permeability powder core provided by an embodiment of the present disclosure;
[0040] Fig.14 It is a schematic diagram of a gapless ferrite core manufactured by a micro-nano flux bridge method provided by an embodiment of the present disclosure;
[0041] Fig.15 It is a schematic diagram of a magnetic coupling mechanism manufactured by using a micro-nano flux bridge method provided in an embodiment of the present disclosure. DETAILED DESCRIPTION
[0042] The embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.
[0043] The following describes the embodiments of the present disclosure through specific examples, and those skilled in the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. The present disclosure can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present disclosure. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present disclosure.
[0044] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement a device and / or practice a method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0045] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the aspects described may be practiced without these specific details.
[0046] Aiming at the magnetothermal degradation problem of array ferrite cores, the present invention proposes a micro-nano flux bridge method with powder core filling air gaps. The magnetic powder core at the air gap is used to restrain the leakage magnetic flux, so as to reduce the concentration of magnetic density around the air gap, thereby alleviating the magnetothermal degradation problem caused by the air gap.
[0047] Micro-nano flux bridge (proper term): Nanocrystalline powder material (nanoscale) is filled between ferrite blocks to remove the air gap between magnetic blocks, thus establishing a propagation bridge for the magnetic flux between magnetic blocks.
[0048] Figure 1 A schematic diagram of a method flow for alleviating magnetic thermal degradation of a magnetic core based on a micro-nano flux bridge provided in an embodiment of the present disclosure.
[0049] like Figure 1 As shown, firstly, a finite element multi-physics field magnetothermal simulation analysis is performed;
[0050] In an embodiment of the present invention, the finite element multi-physics field magnetothermal simulation analysis includes: calculating the relationship between the width of the air gap filled with the magnetic conductive powder, the relative magnetic permeability of the magnetic conductive powder and the magnetothermal characteristics of the ferrite core.
[0051] In the embodiment of the present invention, the relationship between the width of the air gap filled with magnetic conductive powder, the relative magnetic permeability of the magnetic conductive powder and the magnetocaloric characteristics on the ferrite core is calculated based on the following formula:
[0052]
[0053] Among them, T gm (l g ,μ gap ) is the edge temperature rise of the ferrite; p is the order of the air gap width; q is the order of the relative magnetic permeability of the powder core; k pq is the coefficient of the fitted polynomial function; l g is the air gap width; μ gap is the relative magnetic permeability of the medium in the air gap.
[0054] In an embodiment of the present invention, the method further includes: selecting the gap width of the ferrite block before filling and the magnetic powder core used to remove the air gap based on the threshold value of the ferrite edge temperature rise.
[0055] Secondly, an array-type ferrite magnetic block core is manufactured based on the simulation results;
[0056] Next, the magnetic powder core is filled into the air gap of the array-type ferrite magnetic block core;
[0057] Finally, AB glue is injected into the magnetic powder core to form a gapless magnetic core.
[0058] In an embodiment of the present invention, the method further includes: assembling an energy transmission coil; and packaging the magnetic core and the coil.
[0059] In the embodiment of the present invention, the width of the gap between the ferrite blocks is less than 0.4 mm.
[0060] In an embodiment of the present invention, the magnetic powder core is a FeSi6.5 nanocrystalline powder core.
[0061] The present invention is verified by examples below.
[0062] like Figure 2 The magnetic field shown in the figure gathers at the air gap of the ferrite block because the magnetic field is refracted at the interface of different transmission media. The refraction principle is as follows: Figure 3 As shown in (a), the boundary law followed by the magnetic field at the interface of different media is
[0063]
[0064] Among them, μ1 and μ2 represent the relative magnetic permeabilities of the two media, and α1 and α2 represent the refraction angles of the magnetic field in the two media.
[0065] In the array ferrite core, when the magnetic field propagates from the inside of the ferrite to the air gap, due to the large difference in the relative permeability of the two media, there is always α2<<α1, and it is usually expressed as α1≈90°, α2≈0°, which makes the ferrite edge magnetic field almost parallel to the interface and very dense, such as Figure 3 Therefore, the concentration of the magnetic field can be alleviated by reducing the refraction angle of the magnetic field at the interface between the ferrite and the air gap.
[0066] In the traditional calculation model, the magnetic flux density in the magnetic core is determined by the number of turns of the coupling coil and the current flowing through the coil. Figure 3 (a) It can be further concluded that the edge flux density of the array ferrite core is also related to the air gap width l g And the relative magnetic permeability of the air gap μ gap Therefore, the magnetic flux density B at the ferrite core area 1 is area1 Can be defined as
[0067] B area1 ∝NIl g p μ gap q (2)
[0068] Where N is the number of turns of the coupling coil, I is the current in the coil, μ gap Indicates the relative magnetic permeability of the medium at the air gap. It is further considered that the temperature rise at the edge of the ferrite is determined by the relative magnetic permeability of the air gap and the width of the air gap, that is,
[0069] T gm (l g ,μ gap )=∑∑k pq l g p μ gap q (3)
[0070] Therefore, on the premise of a determined air-gap width, improving the relative permeability at the air gap is the key to solving the problem of local overheating of the magnetic core. At the same time, since the magnetic powder core is introduced at the air gap, the magnetic flux leakage at the air gap and the magnetic field concentrated at the edge of the ferrite will be guided from ferrite 1 to ferrite 2, as Figure 4 shown. This greatly reduces the magnetic flux leakage at the air gap and improves the electromagnetic safety of the magnetic coupling mechanism.
[0071] Figure 4 (a) represents the magnetic field propagation model before filling the magnetic powder core. B represents the magnitude of the magnetic field inside ferrite 1, and e x represents its propagation direction. B1 represents the magnitude of the magnetic field concentrated at the edge of the ferrite, and e α1 represents its propagation direction. B2 represents the magnitude of the magnetic field entering the air gap, and e α2 represents its propagation direction, where B = B1 + B2. B3 represents the magnitude of the magnetic flux leakage near the air gap, and e α3 represents its propagation direction. B4 represents the magnitude of the magnetic field entering ferrite 2, and e α4 represents its propagation direction, where B2 = B3 + B4. Figure 4 (b) represents the magnetic field propagation model after filling the magnetic powder core. The meanings represented by each parameter are the same as those in Figure 4 (a), where B' = B. Due to the addition of the magnetic powder core at the air gap, the angle between B 1' and the interface of the propagation medium becomes smaller. Therefore, the degree of magnetic flux density concentration at the edge of the ferrite decreases, and thus B 1' < B1. At the same time, the magnetic powder core also has the function of guiding the magnetic flux leakage at the air gap into ferrite 2, so B 2' > B2, B3' < B3, B 4' > B4. At this time, the magnitude of the magnetic flux leakage at the ferrite air gap is reduced. In summary, after adopting the micro-nano magnetic flux bridge (powder core filling the air gap) method, the degree of magnetic flux density concentration at the edge of the ferrite air gap can be effectively reduced, and the magnetic core loss, temperature rise, and magnetic flux leakage magnitude at the edge of the ferrite air gap can be reduced.
[0072] As Figure 5As shown, a micro-nano flux bridge air-gapless array ferrite core wireless power transmission magnetic coupling machine in an embodiment of the present invention includes: (1) a ferrite block at the receiving end, (2) a receiving coil, (3) a transmitting coil, (4) a ferrite block at the transmitting end, (5) an air gap between the ferrite blocks, and (6) a magnetic powder core. After the ferrite blocks at the (1) receiving end are arranged in an array, the magnetic powder core (6) is filled into the air gap between the ferrite blocks (5) to form the (7) air-gapless array ferrite core at the receiving end. Similarly, the magnetic powder core (6) at the transmitting end is filled into the air gap between the ferrite blocks at the (4) transmitting end to form the (8) air-gapless array ferrite core at the transmitting end. (7) The receiving end gapless array ferrite core and (2) the receiving coil together form the power receiving end in the wireless power transmission magnetic coupling mechanism, and (8) the transmitting end gapless array ferrite core and (3) the transmitting coil together form the power transmitting end in the wireless power transmission magnetic coupling mechanism. In addition, (6) the magnetic powder core is a powder core made of nano-scale soft magnetic materials such as nanocrystals, whose magnetic permeability is greater than that of air, that is, a bridge for conducting magnetic flux between ferrite blocks at the micro-nano level, referred to as a micro-nano flux bridge.
[0073] There is a problem of uneven distribution of magnetic field and thermal field in the wireless charging system. The method of alleviating magnetic and thermal degradation of the magnetic core based on a micro-nano flux bridge proposed in the present invention can balance the magnetic and thermal distribution of the magnetic core to a certain extent.
[0074] The present invention has the following advantages:
[0075] 1. Magnetic heat relief effect on the core surface:
[0076] Figure 6 Respectively represent l g =0.3mm filled with magnetic powder cores with different relative magnetic permeabilities (μ gap =1, 5, 50), the distribution of magnetic flux density and temperature rise on the outer surface of the ferrite at the receiving end. It can be seen that the addition of the magnetic powder core can effectively improve the concentration of magnetic flux at the edge of the ferrite.
[0077] Depend on Figure 7 , Figure 8 It can be seen that under the same 11kW / 85kHz excitation, the overall temperature of the core is reduced after the micro-nano flux bridge method is adopted. At the same time, the temperature rise at the edge of the air gap is significantly suppressed, and the hot spots on the ferrite core are significantly reduced, which improves the safety and stability of the core's high-power and long-term operation.
[0078] 2. Magnetic leakage mitigation effect:
[0079] like Fig. 9 Indicates the air gap flux leakage density B when the same parameter magnetic powder is filled under different air gap widths gThe distribution change diagram along the reference line. The results show that, except for the edge of the magnetic core, the intersection of the air gap is still the highest position of magnetic flux leakage, but the addition of the magnetic powder core effectively reduces the leakage flux of the air gap. g =0.3mm as an example, the maximum value of magnetic flux leakage near the air gap before and after the addition of the magnetic powder core is reduced by 48.1%, which shows that the magnetic powder core confines the air gap leakage magnetic flux within the working area, thereby reducing the leakage magnetic flux.
[0080] 3. System transmission efficiency improvement effect:
[0081] Fig.10 is the equivalent circuit of the magnetic coupling mechanism after powder core filling, ζ1~ζ5 represent the factors of increase of the mutual inductance, self-inductance and equivalent resistance of the transmitting and receiving cores due to the filling of the powder core. τ1~τ5 represent the factors of increase of the mutual inductance, self-inductance and equivalent resistance of the transmitting and receiving cores due to the change of air gap, and τ1~τ3 are all less than 1. The system transmission efficiency and efficiency fluctuation can be expressed as:
[0082]
[0083] Among them, R' tx =ζ4τ4R tx-core +R tx-coil , R' rx =ζ5τ5R rx-core +R rx-coil The addition of powder core reduces the magnetic flux density of ferrite, so ζ4=ζ5<1, that is, R' tx =R' rx <R tx =R rx η1′ is the transmission efficiency of the WPT system after adopting the micro-nano flux bridge method, ω0 is the system operating angular frequency, R L is the load at the receiving end of the WPT system, τ1 is the influence factor of the air gap change on the mutual inductance between the transmitting and receiving ends of the system, τ4 is the influence factor of the air gap change on the equivalent resistance of the magnetic core at the transmitting end of the system, R tx-coil is the equivalent resistance of the transmitting coil when there is no air gap, τ5 is the influence factor of the air gap change on the equivalent resistance of the magnetic core at the receiving end of the system, R rx-core is the equivalent resistance of the receiving end core when there is no air gap, and its value is the ratio of the receiving end core loss to the square of the receiving end current, R rx-coil is the equivalent resistance of the receiving coil when there is no air gap, Δη′ is the system efficiency fluctuation caused by the change of air gap and magnetic powder core, η′1 is the system efficiency when the air gap and magnetic powder core change, η2 is the system transmission efficiency when the magnetic core has no air gap, Δη is the system efficiency fluctuation caused by the change of air gap, and η1 is the system efficiency when the air gap changes. Fig.11The figure shows the variation curve of ζ1τ1M after filling the powder core under different air gap widths. It can be seen that the addition of the powder core increases the mutual inductance of the magnetic coupling mechanism and thus improves the stability of the system transmission efficiency, that is, η1'>η1, Δη'<Δη.
[0084] The specific embodiments of the present invention are as follows:
[0085] Firstly, the magnetothermal bidirectional coupling model of wireless power transmission magnetic coupling mechanism is built with the help of COMSO finite element simulation software. Figure 5 (a) is shown. Based on the simulation model, the influence of the air gap width filled with magnetic powder and the relative magnetic permeability of the magnetic powder on the magnetothermal characteristics of the ferrite core is studied. The research results show that when the air gap width is filled with magnetic powder with a relative magnetic permeability of 50 within 0.4mm, the maximum temperature and leakage magnetic size of the ferrite core are effectively reduced.
[0086] Then follow Figure 1 Flowchart: First build the array ferrite core as Fig.12 It is worth noting that when splicing ferrite blocks, they should be as close as possible to ensure that the spacing between magnetic blocks is within 0.4mm.
[0087] Secondly, prepare magnetic powder with relative magnetic permeability higher than air, such as CZ-8 nanocrystalline powder core and FeSi6.5 nanocrystalline powder core. Fig.13 As shown. Pay attention to selecting magnetic powder with the highest relative magnetic permeability possible, among which the relative magnetic permeability of FeSi6.5 nanocrystalline powder core is 48.73, and FeSi6.5 nanocrystalline powder core is selected as the filling powder core.
[0088] Secondly, the magnetic powder is mixed with AB glue and filled into the array ferrite air gap. Fig.14 shown.
[0089] Finally, the gapless ferrite core and the energy transfer coil are matched to form a magnetic coupling mechanism such as Fig.15 shown.
[0090] The above is only a specific implementation of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present disclosure should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A method for alleviating magnetic core magnetic thermal degradation based on a micro-nano flux bridge, characterized in that: The method comprises the following steps: Conduct finite element multi-physics field magnetic and thermal simulation analysis; An array type ferrite magnetic block core is manufactured based on the simulation results; Filling the air gap of the array-type ferrite magnetic block core with a magnetic powder core; Injecting AB glue into the magnetic powder core to form a gapless magnetic core.
2. The method for alleviating magnetic core magnetic thermal degradation based on micro-nano flux bridge according to claim 1 is characterized in that: The method further comprises: Assemble the energy transmission coil; Encapsulate the core and coil.
3. The method for alleviating magnetic core magnetic thermal degradation based on micro-nano flux bridge according to claim 1 is characterized in that: The finite element multi-physics field magnetic-thermal simulation analysis comprises: Calculate the relationship between the air gap width filled with magnetic powder, the relative magnetic permeability of the magnetic powder and the magnetocaloric properties of the ferrite core.
4. The method for alleviating magnetic core magnetic thermal degradation based on micro-nano flux bridge according to claim 3 is characterized in that: The relationship between the width of the air gap filled with magnetic powder, the relative magnetic permeability of the magnetic powder and the magnetocaloric properties of the ferrite core is calculated based on the following formula: Among them, T gm (l g ,μ gap ) is the edge temperature rise of the ferrite; p is the order of the air gap width; q is the order of the relative magnetic permeability of the powder core; k pq is the coefficient of the fitted polynomial function; l g is the air gap width; μ gap is the relative magnetic permeability of the medium in the air gap.
5. The method for alleviating magnetic core magnetic thermal degradation based on micro-nano flux bridge according to claim 4 is characterized in that: The method further comprises: The gap width of the ferrite block before filling and the magnetic powder core used to remove the air gap are selected based on the threshold of the ferrite edge temperature rise.
6. The method for alleviating magnetic core magnetic thermal degradation based on micro-nano flux bridge according to claim 1 is characterized in that: The gap width between the ferrite blocks is less than 0.4mm.
7. The method for alleviating magnetic core magnetic thermal degradation based on a micro-nano flux bridge according to any one of claims 1 to 5, characterized in that: The magnetic powder core is a FeSi6.5 nanocrystalline powder core.